2011
DOI: 10.1111/j.1758-2229.2011.00291.x
|View full text |Cite
|
Sign up to set email alerts
|

Driving forces behind the biotope structures in two low-temperature hydrothermal venting sites on the southern Mid-Atlantic Ridge

Abstract: Although it has been more than 30 years since the discovery of deep-sea hydrothermal vents, comprehending the interconnections between hydrothermal venting and microbial life remains a challenge. Here we investigate abiotic-biotic linkages in low-temperature hydrothermal biotopes at Desperate and Lilliput on the southern Mid-Atlantic Ridge. Both sites are basalt-hosted and fluids exhibit the expected chemical signatures. However, contrasting crustal permeabilities have been proposed, supporting pervasive mixin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(59 citation statements)
references
References 46 publications
2
57
0
Order By: Relevance
“…They can also explain the hydrogen consumption measured in incubations with Lilliput hydrothermal fluids, which were enriched with T. crunogena (28%) at the end of the experiments (Perner et al, 2011). In fact, in these incubations hydrogen consumption to CO 2 fixation ratios suggested that hydrogen would be fueling biomass production, but due to the absence of experiments demonstrating that Thiomicrospira can indeed oxidize hydrogen and due to relatively high sulfide concentrations in the hydrothermal fluids used for inoculating the incubations, oxidation of residual sulfide was postulated to be responsible for primary production (Perner et al, 2011).…”
Section: Environmental Implicationsmentioning
confidence: 91%
“…They can also explain the hydrogen consumption measured in incubations with Lilliput hydrothermal fluids, which were enriched with T. crunogena (28%) at the end of the experiments (Perner et al, 2011). In fact, in these incubations hydrogen consumption to CO 2 fixation ratios suggested that hydrogen would be fueling biomass production, but due to the absence of experiments demonstrating that Thiomicrospira can indeed oxidize hydrogen and due to relatively high sulfide concentrations in the hydrothermal fluids used for inoculating the incubations, oxidation of residual sulfide was postulated to be responsible for primary production (Perner et al, 2011).…”
Section: Environmental Implicationsmentioning
confidence: 91%
“…Microbial communities in relatively low-temperature diffusing hydrothermal fluids have been investigated in a wide variety of geographically diverse hydrothermal systems (Huber and Holden 2008;Huber et al 2009;Perner et al 2011Perner et al , 2013aPerner et al , 2013bAkerman et al 2013;Campbell et al 2013). These are mainly planktonic free-living communities under conditions in which the endmember fluids have already mixed with infiltrated seawater in relatively shallow subseafloor environments in the recharge and discharge regions of hydrothermal fluids (Bemis et al 2012).…”
Section: Diffusing Hydrothermal Fluidsmentioning
confidence: 99%
“…Thus, it is challenging to clearly understand the relationships between the diversity and composition of the observed microbial populations and hydrothermal fluid chemistry based on existing biological and geochemical data for diffusing fluid habitats. However, several studies have recently suggested the dominance of sulfur oxidizers in typical MOR-B settings and the presence of hydrogen oxidizers in MOR-U settings (Perner et al 2011(Perner et al , 2013aAkerman et al 2013). These results are generally consistent with our thermodynamic predictions of relationships among microbial metabolisms and functions, hydrothermal fluid chemistry, and geological background.…”
Section: Diffusing Hydrothermal Fluidsmentioning
confidence: 99%
“…Previous studies incubating vent fluids at both in situ temperature and pressure are, to our knowledge, limited to an experiment conducted by Wirsen et al (1986). Therefore, this study greatly expands the range of data and can be used for comparison of rates to recent studies that were not carried out at in situ pressure (Bourbonnais et al, 2012;Perner et al, 2010Perner et al, , 2011Perner et al, , 2013.…”
Section: Rates Of Chemosynthetic Processes At In Situ Pressure and Tementioning
confidence: 90%